Social Capital and the Competitiveness of Logistics Enterprises in the Post-pandemic Era of Society 5.0 - Brzozowska, Marta; Kaczmarska-Krawczak, Jadwiga; Kolasińska-Morawska, Katarzyna; Stroińska, Ewa (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The aim of the article is to identify and determine the importance of social capital markers relevant to logistics companies in the face of ecosystem challenges, as well as to recommend pro-competitive activities of the industry in the context of building a Society 5.0. The authors hypothesised that the identification of a set of social capital markers collected in the form of a model may become an instrument supporting the management of a logistics enterprise in line with the Society 5.0 trend. Research Design & Methods: In the research process, a nomothetic approach was used based on the mixed research strategy. The qualitative approach included the method of ethnomethodology with the analysis of available publications, reports and netographic sources. The technique of semantic analysis, the coexistence of terms and the publication suitability of sources were used. On the other hand, the quantitative approach was based on the diagnostic survey method with the CAWI online survey technique. Findings: The conducted research shows the need to ensure the well-being of employees and the development of their competences, especially digital ones in the context of work technologisation, implementation of innovative technological solutions in the logistics industry. Employees of logistics companies notice that digital competences are the element that affects the efficiency of their work, and this again translates into the company’s competitiveness. Implications / Recommendations: The authors recommend actions by the logistics industry that will be aimed at increasing the share of expenditure on the development of social capital by caring for the well-being of employees, developing their talents, competences and skills. A simplified model of the identification of social capital markers in logistics enterprises may be a helpful management instrument in this respect. Contribution: Social capital is of significant importance for the competitiveness of logistics companies in the post-pandemic era of Society 5.0. A high level of trust and cooperation among employees, suppliers, and customers can contribute to more efficient functioning of logistics companies. Social capital can be a key factor in enabling logistics companies to quickly adapt to changing market conditions. Building strong relationships with business partners can bring benefits such as better coordination of activities, greater flexibility, and faster responses to market changes. Investing in the development of social capital can contribute to increasing the competitiveness of logistics companies and lead to their success in the post-pandemic era of Society 5.0.